(3TQM GdSde GdeQhfb aj GdefWbs - (3GdCNVQj, YHO GdQMef Hf eMeO Hf eMeO J (B983 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj LYd bdhH GdYdeGA SehGJ JJLd HgG TehS GdeYGQa CeG HYO adeG hVYJ GdCQLhRI GdeSeGI HGdSde GdeQhfb Ydi GdefWb QGhOfj HYV GdENhGf Ydi Cf CVY YdjgG TQMG aCLHJg Edi Pdc s
(3BNQgG (B:s
(3Edi ehVhYGJgG EjLGHjI cGfJ Cj jHQge YdjgG aj Pdc GdYde Cf cGfJ fSHjI hGddg CYde HGdUhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 331s
(3eYLe GdeDdajf (B2 / 119s
(3cTa GdXfhf (B2 / 998s
(3gOjI GdYGQajf (B6/ 546s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs